2019
DOI: 10.5194/tc-13-2673-2019
|View full text |Cite
|
Sign up to set email alerts
|

Kinematic response of ice-rise divides to changes in ocean and atmosphere forcing

Abstract: Abstract. The majority of Antarctic ice shelves are bounded by grounded ice rises. These ice rises exhibit local flow fields that partially oppose the flow of the surrounding ice shelves. Formation of ice rises is accompanied by a characteristic upward-arching internal stratigraphy (“Raymond arches”), whose geometry can be analysed to infer information about past ice-sheet changes in areas where other archives such as rock outcrops are missing. Here we present an improved modelling framework to study ice-rise … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 13 publications
(24 citation statements)
references
References 40 publications
2
22
0
Order By: Relevance
“…In fact, there is observational evidence for an increase in erosion with snowfall. For example a recent study by Souverijns et al (2018), who used a set of remote-sensing instruments at a study site close to PEA station, found that snowfall events only led to accumulation 60 % of the time, while leading to ablation 40 % of the time due to the erosion of the freshly fallen snow, and confirmed earlier studies in that the availability of fresh snow is more important for erosion to occur than high wind speeds (Gallée et al, 2001).…”
Section: Discussionsupporting
confidence: 72%
“…In fact, there is observational evidence for an increase in erosion with snowfall. For example a recent study by Souverijns et al (2018), who used a set of remote-sensing instruments at a study site close to PEA station, found that snowfall events only led to accumulation 60 % of the time, while leading to ablation 40 % of the time due to the erosion of the freshly fallen snow, and confirmed earlier studies in that the availability of fresh snow is more important for erosion to occur than high wind speeds (Gallée et al, 2001).…”
Section: Discussionsupporting
confidence: 72%
“…The location of the EDML ice core is about 700 km to the south-east of the modelling domain on the Antarctic plateau. The Ekström catchment also contains two ice rises (Schannwell et al, 2019;Drews et al, 2013) with ice flow centres independent from the main ice sheet. Ice rises archive the regional ice sheet history in their internal stratigraphy.…”
Section: The Ekström Catchment Dronning Maud Land East Antarcticamentioning
confidence: 99%
“…The risk involved is that the matching may overcompensate for the simplified model physics, leading to higher uncertainties in future predictions where model constraints are absent. Due to the high computational demands, in terms of both mesh resolution and the physics required to solve for a freely evolving grounding line (Gillet-Chaulet et al, 2012;Seddik et al, 2012;Favier et al, 2014;Schannwell et al, 2019), FS models up to now have been restricted to individual simulations and simulation lengths of < 1000 years for real-world geometries. Therefore, there is a need to extend the applicability of regional FS ice sheet models to timescales longer than 1000 years so that uncertainties due to physical approximations in the force balance can be quantified and reduced in the near future.…”
Section: Introductionmentioning
confidence: 99%
“…The stationary basal friction coefficients have been derived from satellite data in this way for many glaciers and continental ice sheets using velocity data in, e.g., Gillet-Chaulet et al (2016), Isaac et al (2015), Schannwell et al (2019), and Sergienko and Hindmarsh (2013).…”
Section: G Cheng and P Lötstedt: Sensitivity Analysis Of Ice Sheet mentioning
confidence: 99%
“…In an ill-conditioned problem, the sensitivity at the surface to perturbations at the base is low. This matrix can also be used to quantify the uncertainty in the ice flow due to uncertainties in the model parameters (see, e.g., Bulthuis et al, 2019;Schlegel et al, 2018;Smith, 2014). Perturbations at the ice base with short wavelength are propagated to the surface with a weaker effect on the height and velocity compared to long wavelengths in Gudmundsson (2003Gudmundsson ( , 2008.…”
Section: G Cheng and P Lötstedt: Sensitivity Analysis Of Ice Sheet mentioning
confidence: 99%